The impact of isolated maternal hypothyroxinaemia on the incidence of large‐for‐gestational‐age infants: the Ma'anshan Birth Cohort study. (14th February 2018) - Zhu, Y‐d; Han, Y; Huang, K; Zhu, B‐b; Yan, S‐q; Ge, X; Zhou, S‐s; Xu, Y‐y; Ren, L‐i; Sheng, J; Pan, W‐j; Hao, J‐h; et al.
Abstract : Objective: The purpose of this study was to investigate whether isolated maternal hypothyroxinaemia (IMH) is associated with risks of small/large‐for‐gestational‐age (SGA/LGA) infants. Design: Population‐based prospective cohort study. Setting: Ma'anshan Maternal and Child Health (MCH) clinics, China. Population: Pregnant women with singleton births ( n = 3178). Methods: Descriptive statistics were calculated for the demographic characteristics of the mothers and their newborns. Linear regression was applied to estimate the association between thyroid hormone levels and birthweight. Logistic regression was performed to calculate the association between IMH and SGA/LGA. Main outcome measures: Outcomes included SGA/LGA. Results: The prevalence of IMH, defined as a free thyroxine value (FT4) lower than the 2.5th percentile with normal thyroid stimulating hormone, was 2.5% (78/3080) and 2.5% (74/2999) in the first and second trimesters, respectively. Additionally, 306 (9.6%) and 524 (16.5%) infants were defined as SGA and LGA, respectively. No evidence supported the notion that IMH is associated with an increased risk for SGA in either the first [odds ratio (OR): 1.762, 95% confidence interval (CI): 0.759–4.089] or the second (OR: 0.763, 95% CI: 0.231–2.516) trimester. However, an increased risk of LGA was observed among IMH women in the second trimester (OR: 2.088, 95% CI: 1.193–3.654). Maternal TPO‐Ab positivity in the second trimester increased the risk of SGA (OR: 2.094, 95% CI: 1.333–3.290). Conclusion: This study provides evidence that IMH is associated with LGA. Funding: This work was supported by the National Natural Science Foundation of China (No. 81330068). Tweetable abstract: Isolated maternal hypothyroxinaemia may increase the risk of large‐for‐gestational‐age infants. Tweetable abstract: Isolated maternal hypothyroxinaemia may increase the risk of large‐for‐gestational‐age infants.